Materialistic values and well-being among Greek adolescents - Kornilaki, Ekaterina N. (Psychology: the Journal of the Hellenic Psychological Society, 2021)
The aim of this study is to examine the prevalence of materialistic values among Greek adolescents and its associations with well-being measures, such as life satisfaction and self-esteem. Materialistic values were investigated within the wider context of their life goals and aspirations. A growing body of evidence in adults suggests that a strong focus on materialistic values is associated with low self-esteem, depression, problems of psychosocial adjustment and lower life satisfaction. Four hundred sixty-eight adolescents aged 13-15 years completed a structured questionnaire entailing the Material Values Scale (Richins, 2004), Rosenberg’s (1965) global Self-esteem Scale and the Satisfaction with Life Scale (Diener et al., 1985). Young adolescents’ life goals and aspirations were measured with the Aspiration Index (Kasser & Ryan, 1993) assessing the relative strength of intrinsic versus extrinsic aspirations. The findings of the study suggest that investment in materialistic values was associated with lower self-esteem and life satisfaction. Materialism was related to extrinsic life aspirations. The interpretation of the findings and their implications on adolescents’ well-being are discussed.